2007
DOI: 10.1292/jvms.69.1077
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Listeria monocytogenes from the Skin of Slaughtered Beef Cattle

Abstract: ABSTRACT. We attempted to isolate Listeria monocytogenes from skin, contents of large intestines and carcasses of cattle introduced to a slaughterhouse in order to identify source of contamination for this pathogen. Sixty skin samples, 60 samples of the contents of large intestines and 30 carcass samples were colleted in June, August and November 2003 for use in this study. Listeria spp. and L. monocytogenes were isolated from 30 (50%) and 3 (5%) of the cattle skin samples, respectively. However, no Listeria s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
1
9
1
Order By: Relevance
“…Bacterial strains : In this study, we used 67 L. monocytogenes strains [15, 31, 34, 35]. These strains were isolated from skin of beef cattle from a Japanese farm (five strains), Japanese patients with listeriosis (seven strains) and meat produced in Japan (37 strains) or imported to Japan from other countries (18 strains) (Table 1…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacterial strains : In this study, we used 67 L. monocytogenes strains [15, 31, 34, 35]. These strains were isolated from skin of beef cattle from a Japanese farm (five strains), Japanese patients with listeriosis (seven strains) and meat produced in Japan (37 strains) or imported to Japan from other countries (18 strains) (Table 1…”
Section: Methodsmentioning
confidence: 99%
“…RFLP analysis : Genomic DNA from L. monocytogenes was extracted and purified as previously described [24, 25, 31, 33]. For RFLP analysis, genomic DNA was digested with restriction enzymes Xba I, Cla I ( Ban III) or Pst I according to the manufacturer’s instructions (Takara Bio, Otsu, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The occurrence of L. monocytogenes in fresh beef was also established by several studies. [5][6][7] L. monocytogenes is a ubiquitous organism, able to survive and multiply at refrigeration temperatures, in up to 12-13% salt, while certain strains may grow in water activity down to 0.9 and a pH value down…”
Section: Introductionmentioning
confidence: 99%
“…The result suggests that the within-farm prevalence of L. monocytogenes is very low and that samples of more than 10 animals are needed to determine the presence of L. monocytogenes on a given dairy farm. Takahashi et al [22] reported that L. monocytogenes was isolated from the skins of three (5%) of 60 beef cattle sampled at an abattoir, although L. monocytogenes isolates were not obtained from large intestinal contents. Ochiai et al [17] reported that L. monocytogenes was isolated from 15.5% (17/110) of retailed beef samples and that the serovars of the isolates were 1/2a (three isolates), 1/2b (two isolates), 1/2c (eight isolates) and 4b (five isolates).…”
mentioning
confidence: 99%